"Moral Revenge of the Crowd” in the 1854 Revolution in Madrid - Zozaya-Montes, Maria (2013)
The 1854 revolution in Spain has been relatively little studied. Here we try to understand and explain the phenomenon from a Cultural History perspective. In 1854 Spain suffered several Progresist-cut revolutions which took place caused by an unsustainable situation: the Conservative groups (called moderates) had held power for ten years, with politics of its last years being a nest of corruption, ornamented with anti-constitutional nuances. The situation was worsened by a famine, which stimulated a military led revolution, followed by a popular uprising. This was successful in Madrid, and promptly extended from here to various Spanish provinces. This article analyses the attacks that took place against the Conservative power groups. Studies the war in the streets, looking for popular justice in a sort of moral revenge of the multitude (paraphrasing Edward P. Thompson’s expression), by selectively targeting the symbols of power. It takes into account the collective mentalities, the constructive processes leading to the representations of power, the systems leading to the resistance against it and the mobilisation of the masses, with the specific manner of assimilation Liberalism undertook to put popular justice in place. The result was the triumph of Liberalism, which would sustain power between 1854 and 1856 (progressive biennium), popular victory that transformed the way the power looked back to that revolution.